11 A service improvement project to optimise the perioperative pathway for emergency laparotomy in extremely low birthweight neonates at great ormond street hospital. (22nd November 2019) - Dawes, Joy; Stevens, Paul; Blackburn, Simon; Cross, Kate; Hannam, Simon; Howard, Richard
Abstract : Background: Emergency neonatal laparotomy in extremely low birthweight neonates (<1 kg) is challenging and associated with significant morbidity and mortality. Evidence suggests that transferring these critically ill neonates to theatre results in deterioration in physiological parameters. Operating on NICU is likely to reduce these risks. Aims: There is no standard of care at GOSH regarding operative location, optimal preparation (e.g. vascular access), intraoperative management and team roles and responsibilities. This project was designed to streamline the perioperative pathway to improve outcomes for these complex neonates. Methods: A Neonatal Surgery Improvement groupwas established consisting of surgeons, neonatologists, anaesthetists, NICU and theatre staff. Retrospective datawas collected over a 31 month period to investigate the frequency of cases, location of surgery and early morbidity and mortality. An Anaesthetic Consultant Survey was undertaken to obtain feedback regarding perioperative management. A neonatal laparotomy rehearsal took place on NICU to define optimal positioning, equipment and roles. We collaborated with 2 other tertiary paediatric hospitals (including site visit) and the Pan London Neonatal Network to share experiences. Results: A new guideline for emergency laparotomy on NICU was written to standardise perioperative care (figure 1 ). Checklists for NICU nurses and anaesthetists were constructed and all stakeholders received education. A neonatal anaesthesia trolley was designed for use on NICU. Conclusion: We are obtaining formal feedback as part of the Surgical Safety Checklist Team Brief which will allow us to improve the guideline going forward. Prospective data collection is also underway to assess the impact of our service improvement measures. Informal feedback from the MDT has been overwhelmingly positive to date, including improved communication and team working across specialties. Acknowledgements: Many thanks also go to Joe Curry, Stefano Giuliani, Dhanya Mullassery, Paolo De Coppi, Carrie Pennock, Jane Isworth and Laura Kidd for their assistance with this project.